Unravelling the effect of multiple stressors on ecological structure of littoral lake macroinvertebrates. Issue 3 (21st March 2021) - Jurca, Tamara; Donohue, Louise; McGoff, Elaine; Tunali, Saliha Y.; Irvine, Kenneth
Abstract: Morphological alteration of shorelines and eutrophication both affect the biological integrity of European lakes. These pressures, often acting simultaneously, are difficult to tease apart. In this study, we related the number of taxa with specific habitat preference to habitat complexity across lakes of varying nutrient state. Habitat complexity at morphologically altered shorelines was significantly lower than at unaltered sites across trophic categories. A generalised linear mixed‐effects model showed decreased number of taxa with specific mesohabitat preference at morphologically simplified sites in oligotrophic and mesotrophic, but not eutrophic lakes. These results suggest: (1) an antagonistic interaction between the effect of nutrient enrichment and morphological alterations on lake littoral communities and (2) the number of macroinvertebrate habitat specialists could potentially be used to assess the effects of structural simplifications of shorelines in lakes of low to medium nutrient status. We conclude that the use of functional traits approach in aquatic ecology should foster better understanding of stressor–response relationships for combined effect of multiple stressors.